Challenging the status quo: results of an acceptability and feasibility study of hypertensive disorders of pregnancy (HDP) management pathways in Indonesian primary care - Fitriana Murriya Ekawati; Ova Emilia; Jane Gunn; Sharon Licqurish; Phyllis Lau (BMC, 2021)
Abstract Background Hypertensive disorders of pregnancy (HDP) are the leading cause of maternal mortality in Indonesia. Focused HDP management pathways for Indonesian primary care practice have been developed from a consensus development process. However, the acceptability and feasibility of the pathways in practice have not been explored. This study reports on the implementation process of the pathways to determine their acceptability and feasibility in Indonesian practice. Methods The pathways were implemented in three public primary care clinics (Puskesmas) in Yogyakarta province for a month, guided by implementation science frameworks of Medical Research Council (MRC) and the Practical Robust Implementation and Sustainability Model (PRISM). The participating providers (general practitioners (GPs), midwives, and nurses) were asked to use recommendations in the pathways for a month. The pathway implementation evaluations were then conducted using clinical audits and a triangulation of observations, focus groups (FGs), and interviews with all of the participants. Clinical audit data were analysed descriptively, and qualitative data were analysed using a mix of the inductive-deductive approach of thematic analysis. Results A total of 50 primary care providers, four obstetricians, a maternal division officer in the local health office and 61 patients agreed to participate, and 48 of the recruited participants participated in evaluation FGs or interviews. All of the providers in the Puskesmas attempted to apply recommendations from the pathways to various degrees, mainly adopting preeclampsia risk factor screenings and HDP monitoring. The participants expressed that the recommendations empowered their practice when it came to HDP management. However, their practices were challenged by professional boundaries and hierarchical barriers among health care professionals, limited clinical resources, and regulations from the local health office. Suggestions for future scale-up studies were also mentioned, such as involving champion obstetricians and providing more patient education toolkits. Conclusion The HDP management pathways are acceptable and feasible in Indonesian primary care. A further scale-up study is desired and can be initiated with investigations to minimise the implementation challenges and enhance the pathways' value in primary care practice.